IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN MATEMATIKA DI UPTD SMP NEGERI 8 GUNUNGSITOLI - Sari Santi Siapudan Lase; Yakin Niat Telaumbanua; Ratna Natalia Mendrofa; Netti Kariani Mendrofa (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
This research is based on a preliminary study conducted through initial observations at UPTD SMP Negeri 8 Gunungsitoli, which reavealed that teachers are still in the adjustment stage to the independent curriculum, leading to suboptimal implementation. Low student motivation, inadequate mathematics learning facilities and infrastructure, and limited resources encouranged the researcher to investigate the extent of the independent curriculum implementation, learning, and assessment at the school. This study employs a qualitative research method with data colleted through observation, interviews, and documentation. The instruments used included interviews with teacher, student, and several school administration. Data analysis consisted of data reduction, data presentation, and conclusion drawing using qualitative deskriptive analysis techniques. The findings of this research indicate that teachers have prepared learning plans based on the independent curriculum. although the implementation has not been fully optimal. Teachers have integrated the main components of the independent curriculum into the learning process, but some still encounter abstracles due to a lack of facilities and resources. Overall , the independent curriculum has been implemented and has shown positive results in learning, thought improvements are still needed to achieve maximum outcomes.